1990
DOI: 10.1084/jem.172.2.463
|View full text |Cite
|
Sign up to set email alerts
|

Structure and expression of germline epsilon transcripts in human B cells induced by interleukin 4 to switch to IgE production.

Abstract: SummaryInterleukin 4 (11,4)-induced IgE production coincides with the appearance of the 2.2-kb productive e-mRNA, but is preceded by synthesis of a 1 .7-kb e-RNA. Analysis of cDNA copies of the 5' end of this RNA indicated that the 1.7-kb E-RNA is a germline e immunoglobulin heavy chain transcript with an exon mapping 5' to the switch region . Transcription through switch regions has been implicated in the control of class switching . However, IL4 or cloned CD4+ T cells were able to induce germline e transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
168
0
6

Year Published

1995
1995
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 326 publications
(181 citation statements)
references
References 58 publications
7
168
0
6
Order By: Relevance
“…Therefore, the mouse and human GL ⑀ promoters are probably not regulated identically. For example, induction of GL ⑀ transcripts in mouse splenic B cells requires IL-4 plus CD40L or LPS, whereas induction of GL ⑀ transcripts in human peripheral blood B cells requires only IL-4, although the response can be further enhanced by some NF-B inducers (6). In this study, we found AP-1 activity is induced in mouse splenic B cells by CD40L, but we could not detect C/EBP␤ in nuclear extracts from cells either untreated or treated with CD40L for 4 h by Western blotting (data not shown).…”
Section: Regulation Of Ig Gl ⑀ Transcripts Differs Between Mouse and mentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the mouse and human GL ⑀ promoters are probably not regulated identically. For example, induction of GL ⑀ transcripts in mouse splenic B cells requires IL-4 plus CD40L or LPS, whereas induction of GL ⑀ transcripts in human peripheral blood B cells requires only IL-4, although the response can be further enhanced by some NF-B inducers (6). In this study, we found AP-1 activity is induced in mouse splenic B cells by CD40L, but we could not detect C/EBP␤ in nuclear extracts from cells either untreated or treated with CD40L for 4 h by Western blotting (data not shown).…”
Section: Regulation Of Ig Gl ⑀ Transcripts Differs Between Mouse and mentioning
confidence: 99%
“…(6,16). The divergent binding sites for AP-1 in mouse and C/EBP in human are boxed separately, whereas the conserved binding sites for Stat6 (16,19), NF-B (12,16,19), and BSAP (58) Therefore, transient induction of AP-1 and NF-B might be sufficient to support activation of the GL ⑀ promoter by Stat6.…”
Section: Kinetics Of Induction and Half-life Of Gl ⑀ Transcripts In Mmentioning
confidence: 99%
See 1 more Smart Citation
“…The first is delivered by specific cytokines that activate the promoter of the relevant immunoglobulin isotype 22 and the second by CD40L expressed on the CD4 T cells. 23 IL-4 was shown 24 to switch B cells to IgE and subsequently interferon-c was identified as the switch factor for IgG1 in humans 25 and IgG2a in the mouse.…”
Section: How Is Ige Class Switching Controlled?mentioning
confidence: 99%
“…Stimulation of B cells with IL-4 alone induces the expression of germ-line Cf transcripts [8]. The additional signal is required to further induce class switching to IgE, which results in the accumulation of mature (membrane-bound and productive) Cf transcripts leading lo Correspondence: Yukiyoshi Yaoagihara, Clinical Research Centre Ibr Allergy.…”
Section: Introductionmentioning
confidence: 99%